2014
DOI: 10.13102/sociobiology.v61i2.171-177
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence Patterns Between Ants And Spiders In Grassland Habitats

Abstract: The ecological importance of both ants and spiders is well known, as well as the relationship between certain spiders and ants. The two main strategies ˗ myrmecomorphy (ant-mimicking) and myrmecophagy (ant-eating) ˗ that connect spiders to ants have been mostly studied at the behavioural level. However, less is known about how these relationships manifest at the ecological level by shaping the distribution of populations and assemblages. Our question was how ant-mimicking and ant-eating spiders associate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…The correlation between ant-eating spiders and Formicinae ants was higher than the correlation between ant-eating spiders and Myrmicinae ants, and this was also reported by Rákóczi and Samu (2014), who explained that this difference could be related with the different types of defenses that these ant groups exhibit; thus, while Myrmicinae have thick cuticle, cuticle structures, a distinct postpetiole and a functional sting, Formicinae are deprived of postpetiole and functional stings and their defense is based on the use of their strong mandibles and toxin exudation (formic acid or anal gland secretions).…”
Section: Co-occurrence Between Ants and Ant-associated Spiderssupporting
confidence: 53%
See 1 more Smart Citation
“…The correlation between ant-eating spiders and Formicinae ants was higher than the correlation between ant-eating spiders and Myrmicinae ants, and this was also reported by Rákóczi and Samu (2014), who explained that this difference could be related with the different types of defenses that these ant groups exhibit; thus, while Myrmicinae have thick cuticle, cuticle structures, a distinct postpetiole and a functional sting, Formicinae are deprived of postpetiole and functional stings and their defense is based on the use of their strong mandibles and toxin exudation (formic acid or anal gland secretions).…”
Section: Co-occurrence Between Ants and Ant-associated Spiderssupporting
confidence: 53%
“…It was found that both ant-mimicking and anteating spiders were positively correlated with Formicinae ants while only ant-eating spiders were positively correlated with Myrmicinae. Rákóczi and Samu (2014) also only found positive association between ant-mimicking spiders and Formicinae, indicating that this could be related to the numerical dominance of Formicinae, which makes them a better model for Batesian-mimicry.…”
Section: Co-occurrence Between Ants and Ant-associated Spidersmentioning
confidence: 91%